2012
DOI: 10.1111/j.1526-4637.2012.01452.x
|View full text |Cite
|
Sign up to set email alerts
|

How Does Use of a Prescription Monitoring Program Change Medical Practice?

Abstract: Prescribers' use of an electronic PMP may influence medical practice, especially opioid abuse detection, and is associated with clinical responses to suspected doctor shopping or diversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 27 publications
(28 reference statements)
0
43
1
Order By: Relevance
“…Use of state prescription monitoring programs may be helpful in detecting patterns of abuse, diversion, and counseling on safety precautions against addiction and prescription opioid overdose. 23 Our findings indicate a need for providers to be aware of potentially exploitative partnerships, abusive relationships, arrangements in which another person may control or steal their patients' medications, and other types of interpersonal violence such as medication exploitation, when prescribing abusable medications like prescription opioids. Laws in both study areas require healthcare providers to report elder and child abuse.…”
Section: Discussionmentioning
confidence: 99%
“…Use of state prescription monitoring programs may be helpful in detecting patterns of abuse, diversion, and counseling on safety precautions against addiction and prescription opioid overdose. 23 Our findings indicate a need for providers to be aware of potentially exploitative partnerships, abusive relationships, arrangements in which another person may control or steal their patients' medications, and other types of interpersonal violence such as medication exploitation, when prescribing abusable medications like prescription opioids. Laws in both study areas require healthcare providers to report elder and child abuse.…”
Section: Discussionmentioning
confidence: 99%
“…Although clinicians have reported favorable beliefs and attitudes about improvements in pain and quality of life attributed to opioids (159), most consider prescription drug abuse to be a "moderate" or "big" problem in their community, and large proportions are "very" concerned about opioid addiction (55%) and death (48%) (160). Clinicians do not consistently use practices intended to decrease the risk for misuse, such as PDMPs (161,162), urine drug testing (163), and opioid treatment agreements (164). This is likely due in part to challenges related to registering for PDMP access and logging into the PDMP (which can interrupt normal clinical workflow if data are not integrated into electronic health record systems) (165), competing clinical demands, perceived inadequate time to discuss the rationale for urine drug testing and to order confirmatory testing, and feeling unprepared to interpret and address results (166).…”
Section: Clinician and Patient Values And Preferencesmentioning
confidence: 99%
“…In Rhode Island and Connecticut, 17.9% and 37.4% of physicians, respectively, were aware of their state's PMP. 35 In a national survey of medical toxicologists, the results showed that approximately 25% of respondents were unaware of their state's PMP or unsure about the registration process. 36 PAT nonusers had approximately equal numbers of attending and resident EPs, whereas PAT users had considerably more attending EPs versus resident physicians.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, 41% of EPs did not know how to register for access or they were unsuccessful registering for access to the PAT database, which is consistent with the findings of Green et al, who reported that 12% (Rhode Island) and 35.5% (Connecticut) of prescribers did not know how to enroll for their state's PMP. 35 This may indicate a need to simplify the registration process or provide live training for EPs.…”
Section: Discussionmentioning
confidence: 99%